Realidades ficticias: el parque temático y su relación con la industria cinematográfica - Jiménez Morales, Rosario (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
The present article is based on the relationships between theme parks and the cinema industry, since both create common products and share a similar aesthetic experience. Roller coasters, spectacles and lives performances try to bring the cinema into real life using new technologies and elements presented in popular films